Ações parabólicas: uma análise do ensino de Jesus através de suas ações - Kunz, Claiton André (2006)
This dissertation is an analysis of one of Jesus teachings methods. Parabolic actions, which were used by the Old Testament prophets, were also used by Jesus Christ. This research tries to attest this use and establish some criteria for its analysis. In the first part, some general aspects that they concern the parabolic actions are examined, as, for example, their conception, their use, the purpose for which they were used and some of their characteristics. In the second part, some formal aspects of the actions are examined, as, for example, literary form, historical analysis, intentional analysis and interpretation. In this part, especially in the analysis of the literary form, some criteria for the identification of parabolic actions are established. Finally, in the third part, by way of example, the parabolic action of the Cursing of the Fig Tree, as told by Marcos and Matthew, is analysed. Parabolic actions are a preaching method. But, much morethan an aid to preaching or a way of illustrating a message, they themselves are the messages.